Age, pathology and CA-125 are prognostic factors for survival in patients with brain metastases from gynaecological tumours. (September 2020) - Nagtegaal, S.H.J.; Hulsbergen, A.F.C.; van Dorst, E.B.L.; Kavouridis, V.K.; Jessurun, C.A.C.; Broekman, M.L.D.; Smith, T.R.; Verhoeff, J.J.C.
Highlights: The largest cohort of brain metastases patients from gynaecological tumours. CA-125, age and primary tumour type are prognostic for survival. This will inform clinical practice and aid the development of new prognostic tools. Abstract: Background and purpose: Brain metastases originating from gynaecological tumours are a rare phenomenon, but have an increasing incidence due to better targeted therapies. This study aimed to identify factors that predict survival in these patients, which can be used in creating a robust prognostic tool for shared decision making. Materials and methods: We identified a consecutive cohort of 73 patients treated for gynaecological brain metastases in two tertiary institutions. Baseline demographics, pathology and serum CA-125 were included in a multivariable Cox proportional hazards model. Results: Median overall survival in our cohort was 14.4 months, with a one-year survival of 56.4% and a two-year survival of 39.1%. Thirty-eight patients (52.1%) had ovarian carcinoma as the primary malignancy. The following factors were significantly associated with survival: age (HR 1.05 per year), CA-125 (HR 1.02 par 50 U/ml), and uterine and vulvar primary tumours (when compared to ovarian carcinoma, with HRs 3.07 and 8.70). A post-hoc analysis with primary tumour site reclassified into ovary versus non-ovary showed a HR of 0.50 for ovarian primary tumour type. Conclusion: We have found that age, pathology and CA-125 are prognostic factors for survival in patients with brain metastases from gynaecological tumours. Our findings may provide a foundation for future development of prediction models, for the benefit of both patients and physicians.